Benign mesenteric lymphangioma presenting as acute pancreatitis: a case report - Akwei, Solomon (BioMed Central, 2009)
Benign mesenteric lymphangiomas are rare intra-abdominal cysts which may be asymptomatic or present with a variety of abdominal symptoms including an acute abdomen. We are however not aware of any reports in the literature linking mesenteric lymphangioma to acute pancreatitis. We present the case of a 62-year-old man who was admitted with signs and symptoms of acute pancreatitis and a palpable abdominal mass. Computerised tomography (CT) of his abdomen confirmed the presence of a mesenteric cystic mass. He underwent a laparotomy at which a large thin walled mass filled with a chylous fluid was resected. Histological analysis of this cyst showed it to be a benign mesenteric lymphangioma.